AIDS Awareness among Clinical Dental Students of India (Bangladesh Journal of Medical Science, 2013)
Objective: HIV-infected patients, with or without knowledge of their own serologic status are seeking dental care in increasing numbers. Dental students are at the risk of exposure to the HIV infections during their clinical training if adequate and stringent infection control measures. The objective of the present study was to assess the level of understanding and awareness of this disease among the third year clinical dental students at a private dental institution in Mangalore, Karnataka, India. Materials and methods: A cross sectional survey of 100 third year clinical dental students of Karnataka was carried out using a self-administered questionnaire. The questionnaire comprised of sociodemographic details, apart from 8 questions on knowledge and 2 questions on attitude towards HIV/AIDS patient. Descriptive analysis was carried out. Results: The response rate was 100%. Majority of students knew that AIDS is a disease of immunity. About 78% of the students knew that HIV/ AIDS is transmitted by contaminated blood products. Eighty six percent of the subjects knew which test was done to detect AIDS while others were not quite sure of it. Only 15% answered correctly regarding the percentage risk of transmission of HIV to a health care worker following contaminated needle stick injury. Most of the students were either not aware or not sure about the universal precaution measures to be taken while treating an AIDS patient. Conclusion: The results showed that the third year dental students of Karnataka, India had fair knowledge and good attitude regarding HIV/AIDS. However it did reveal some of the inadequacies and misconceptions regarding the disease among the dental students. DOI: http://dx.doi.org/10.3329/bjms.v13i1.14332 Bangladesh Journal of Medical Science Vol. 13 No. 01 January 2014: 20-24